Using abstract interpretation to produce dependable aerospace control software - Silva, Rovedy Aparecida Busquim e (2013)
In the context of software dependability, the software veri- fication process has an important role. Formal verification of programs is an activity that can be inserted in this process to improve software reliability. This paper presents the defini- tion of an approach that employs a formal verification tech- nique based on abstract interpretation. The main goal is to apply this technique as a formal activity in the software veri- fication process to help software engineers identify programs faults. The applicability of the proposed approach is demon- strated by a case study based on embedded aerospace control software. The results obtained from its use show that abstract interpretation can contribute to software dependability.